Intra-household inequality and child welfare in Argentina - Lucía Echeverria; Martina Menon; Federico Perali; Miriam Berges (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2019)
Are two parents and single parents allocating household resources to children in the same way? Which factors affect intra-household inequality? Do mothers re-distribute more income to children as they are more empowered? We focus on child welfare in the context of two parent and single parent families, which is relevant for policy recommendation. We model households behavior in a collective framework, which allows us to understand the rule governing the allocation process between adults and children. Using consumption data from Argentina from three consecutive expenditures surveys (1996, 2004 and 2012) we analyze intra-household behavior over three different socio-economic contexts. We estimate a collective quadratic demand system following a structural approach to identify the fraction of total household expenditure that is devoted to children and adults, exploiting the observability of assignable goods. We provide the first evidence of intra-household inequality and individual poverty levels for Argentina. Our results indicate that family structure matters in the intra-household distribution. We find a positive gender bias in expenditure when children are females for both types of families, and we document that children fare better when mothers have a higher bargaining power in the allocation process, measured by their employment status. Further, we find several features of intra-household behavior which are persistent in time.
Keywords: 330; Collective model; Demand system; Sharing rule; Intra-household resource distribution; Child welfare